Measuring Performance of Teacher Certification Program by Output Target and Intended Impact Achievement - Wahyudi, Kalvin Edo; Supranoto, Supranoto; Suji, Suji (UI Scholars Hub, 2013)
This research aims to evaluate teacher certification program performance in Jember. The focus of attention is measurement of the output of target achievement and the intended impact one. Output target achievement was measured by descriptive analysis. Intended impact achievement refers to the impact of teacher certification program to the education quality. Impact measurement contains 3 steps analysis (comparative, associative, time series). Data were gathered by documentary collecting model in 52 schools (SMPN and SMAN) in Jember. The disproportionate stratified area random technique was used to choose representative samples. The result of descriptive analysis showed that the output target achievement has a low positive performance. The result of impact measurement showed that the teacher certification program has a low positive impact to the education quality. So, this research does not only aim at evaluating teacher certification program performance, but also offers some simple research models for measurement of program performance (output target achievement and intended impact one measurement models).